Creating dynamic web pages with JavaScript and DOM - Svekis, Laurence (Manning Publications, 2022)
Explore how to create amazing mini-projects that help you learn JavaScript. If you want to add interaction or dynamic content to your web pages, this is the course for you! Create amazing content on your pages, driven dynamically with JavaScript. Projects within this course are designed to help you learn more about JavaScript and interacting with the DOM. Learn by example, because the course is loaded with fun projects that demonstrate what you can do with JavaScript. Explore how to write JavaScript code, select page elements, and more. The course covers everything you need to know in a step-by-step format so that you can start coding with JavaScript and create amazing things. Learn about JavaScript and DOM page element manipulation. No libraries, no shortcuts--just learn JavaScript to make dynamic and interactive web applications.